Assessing goodness‐of‐fit for evaluation of dose‐proportionality. (15th October 2020) - Wolfsegger, Martin J.; Bauer, Alexander; Labes, Detlew; Schütz, Helmut; Vonk, Richardus; Lang, Benjamin; Lehr, Stephan; Jaki, Thomas F.; Engl, Werner; Hale, Michael D.
SUMMARY: For the clinical development of a new drug, the determination of dose‐proportionality is an essential part of the pharmacokinetic evaluations, which may provide early indications of non‐linear pharmacokinetics and may help to identify sub‐populations with divergent clearances. Prior to making any conclusions regarding dose‐proportionality, the goodness‐of‐fit of the model must be assessed to evaluate the model performance. We propose the use of simulation‐based visual predictive checks to improve the validity of dose‐proportionality conclusions for complex designs. We provide an illustrative example and include a table to facilitate review by regulatory authorities.